Book Reviews. Issue 1 (1st June 2019) - Gray, Maggie; Ribbens, Kees; Domsch, Sebastian; Jones, Dyfrig
Abstract : Thierry Groensteen, The Expanding Art of Comics: Ten Modern Masterpieces, trans. Ann Miller (Jackson: University Press of Mississippi, 2017). 240 pp. ISBN: 978-1-49-680802-8 ($65) Nina Mahrt, Die Darstellung realer Kriege in Comics (Frankfurt: Peter Lang, 2016). 471 pp. ISBN: 978-3-631-67658-5 (€84.20) Anna Maria Jones and Rebecca N. Mitchell, eds, Drawing on the Victorians: The Palimpsest of Victorian and Neo-Victorian Graphic Texts (Athens: Ohio University Press, 2017). 386 pp. ISBN: 978-0-82-142247-2 ($80) Chris Murray, The British Superhero (Jackson: University Press of Mississippi, 2017). 240 pp. ISBN: 978-1-49-680737-3 ($65)